Exploring the link between perceived physical literacy and academic performance outcomes: insights from the EHDLA study - Domínguez-Martín, Gabriel; Tárraga-López, Pedro J.; López-Gil, José Francisco (Frontiers in Sports and Active Living, 2024)
Objective The aim of this study was to verify the relationship between perceived physical literacy (PPL) and academic performance outcomes among Spanish adolescents aged 12–17 years. Methods This cross-sectional study is a secondary examination utilizing data derived from the Eating Healthy and Daily Life Activities (EHDLA) project. The Spanish Perceived Physical Literacy Instrument for Adolescents (S-PPLI) was used to evaluate the PPL of the participants. To determine academic performance, the numerical grades for each subject were added together and then divided by the total number of subjects. Results Overall, a positive trend in the association between S-PPLI scores and academic performance was observed. We identified two significant ranges within the S-PPLI scores. First, there was a significant range between 9 and 33 points on the S-PPLI, indicating an inverse association with academic performance. Second, another significant range was observed at scores of 34 points or higher on the S-PPLI, suggesting a positive association with academic performance. Participants with low PPL had the lowest academic performance (mean = 6.4; bias-corrected and accelerated (BCa) bootstrapped 95% confidence interval (CI): 6.2–6.6). Conversely, those adolescents with high PPL had the highest academic performance (mean = 6.9; BCa bootstrapped 95% CI: 6.6–7.1). Significant differences were found between low PPL and medium PPL (p-adjusted = 0.031) and between low PPL and high PPL (p-adjusted = 0.031). Conclusions Increased physical literacy could be a relevant factor for achieving greater academic performance in adolescents. This study has potential implications for physical education instructors, school leaders, and healthcare practitioners.